The Development and Characterization of a Human Midgut Carcinoid Cell Line - Van Burenn II, George (2007)
Purpose: Gastrointestinal neuroendocrine tumors (NET) are rare heterogeneous tumors that hypersecrete neuropeptides. The scarcity of good gastrointestinal NET models has limited the ability to study potential therapeutic agents. We describe and characterize the establishment of a human midgut carcinoid tumor cell line carcinoid tumor 2 (CNDT2). Experimental Design: Tumor cells (CNDT2) were isolated from a liver metastasis from a patient with a primary ileal carcinoid. After 9 weeks in culture, the cells were plated in soft agar, and cells from a single colony were put back in culture (CNDT2.1). Those CNDT2.1 cells were injected s.c. into nude mice. Cells were isolated from a single resultant tumor (CNDT2.5), cultured, and characterized by electron microscopy, reverse transcription-PCR, serotonin enzyme immunoassay, Western blotting, and immunohistochemical analysis for NET markers and potential therapeutic targets. Results: CNDT2 cells grew in monolayers in vitro, formed colonies in soft agar, and formed tumors in mice. Electron microscopy revealed round, pleomorphic, electron-dense neurosecretory granules characteristic of NETs. Tumor xenografts exhibited the appearance of NETs with small “salt-and-pepper” nuclei on H&E staining and chromogranin A, synaptophysin, and CD56 on immunohistochemical staining. CNDT2.5 cells produced serotonin and expressed insulin-like growth factor receptor-I, platelet-derived growth factor receptor-β, vascular endothelial growth factor receptor-1, cMET, epidermal growth factor receptor, neuropilin-1, and somatostatin receptors 1 to 5. Cytogenetic analysis revealed the presence of deletions at 2p and 6q and numerous translocations. Conclusion: The establishment of this human midgut carcinoid tumor cell line may serve as a useful model system for studying cell biology and novel targeted agents in preclinical models.